Réponses

2014-03-10T18:56:11+01:00
1)      3(2x-1) = 2-(x-3)        développer
         6x-3= 2-x+3
          6x-3 = 5-x                    isoler le x d'un côté
           6x-(-x) = 5-(-3)
             7x = 8
             x= 8/7                   tu mets le S = 8/7 entre accolade et pareil pour 2)3)4)
                              
                             

2)            5-2(x+3) = 3-x                    développer
               5-2x-6 = 3-x
               -11-2x = 3-x                       isoler le x
               -2x -(-x) = 3-(-11)
               -x = 14
               x= -14


3)          8(x-2) =4(2x-4) - 3x                        développer
             8x-16 = 8x-16-3x
             8x-16 = 5x-16                        isoler le x
              8x-5x = -16-(-16=
               3x = 0
                 x= 0

4)        3(-x+7) = -7(x+3)            développer
          -3x +21 = -7x-21        isoler le x
           -3x-(-7x) = -21-21
           4x = -42
           x= - 42/4
           x = - 21/2